Our kind of traitor [videorecording (DVD)] - Harris, Naomie, 1976-; McGregor, Ewan, 1971-; Skarsgård, Stellan; Le Carré, John, 1931- (Lionsgate, 2016)
While on vacation, a married couple unwittingly befriends a flamboyant and charismatic Russian named Dima, who, unbeknownst to them, is a kingpin money launderer for the mafia. When Dima confides to his new friends that he plans to escape from the mob, they're quickly swept into the dangerous world of international espionage. The unlikely companions must undertake a perilous journey through Paris, Bern, and London in order to save Dima and his family.